2016
DOI: 10.1080/19012276.2016.1198270
|View full text |Cite
|
Sign up to set email alerts
|

The role of students’ prior topic beliefs in recall and evaluation of information from texts on socio-scientific issues

Abstract: In this research, we investigated relationships between undergraduate students' prior topic beliefs and their recall of the main conclusions from texts on controversial socio-scientific issues, to what extent students trusted the recalled conclusions, and how they justified their trust in those conclusions. While belief-biased recall of text conclusions was not observed in this study, students were found to trust the recalled conclusions more when they were consistent than when they were inconsistent with stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The myside bias phenomenon implies that when dealing with controversial issues, people tend to evaluate and generate evidence, as well as test hypotheses, biased by their prior attitudes . Empirical research corroborates this view, with information consistent with people's prior attitudes more likely to be recalled, evaluated positively, and included in mental representations of situations and issues than attitude-inconsistent information (Andiliou, Ramsay, Murphy, & Fast, 2012;, 2014McCrudden & Sparks, 2014;Strømsø, Bråten, & Stenseth, 2015;van Strien, Brand-Gruwel, & Boshuizen, 2014;Wiley, 2005).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The myside bias phenomenon implies that when dealing with controversial issues, people tend to evaluate and generate evidence, as well as test hypotheses, biased by their prior attitudes . Empirical research corroborates this view, with information consistent with people's prior attitudes more likely to be recalled, evaluated positively, and included in mental representations of situations and issues than attitude-inconsistent information (Andiliou, Ramsay, Murphy, & Fast, 2012;, 2014McCrudden & Sparks, 2014;Strømsø, Bråten, & Stenseth, 2015;van Strien, Brand-Gruwel, & Boshuizen, 2014;Wiley, 2005).…”
Section: Introductionmentioning
confidence: 80%
“…Many studies also indicate that despite knowledge about sourcing, students often fail to attend to and evaluate source features when engaged in task-oriented reading involving multiple documents (Britt & Aglinskas, 2002;Strømsø, et al, 2013;Stadtler & Bromme, 2007), and if attending to sources, students have been found to rely on superficial cues such as layout (Iding, et al, 2009) or to adopt a default stance using a general "rule of thumb" (e.g., "I trust documents written by professors and avoid articles written by journalists") (List & Alexander, 2018). The reason that students infrequently undertake a deeper analysis of author expertise is beyond the scope of the current thesis, but individual differences seem to be related to sourcing activities with prior knowledge (Rouet, et al, 1997;Rouet, et al, 1996;Braasch, et al, 2014), interest (Guthrie, et al, 2007), and prior attitudes towards the current reading topic (Strømsø, Bråten, & Stenseth, 2017;Braasch, et al, 2014;Andreassen & Bråten, 2013;Gottlieb & Wineburg, 2012). These connections are particularly relevant to the studies presented in the current thesis (see section 3.1 for further detail).…”
Section: Author Expertisementioning
confidence: 99%
See 1 more Smart Citation
“…To research multimedia learning among adolescent readers, we considered it appropriate to present them with a topic that was both relatively complex and controversial, requiring that students identify different perspectives and integrate them into a coherent understanding. Previous topics used in similar research have concerned possible adverse health effects of consuming artificial sweeteners (Strømsø, Bråten, & Stenseth, 2017) pros and cons regarding the security of nuclear plants (Stenseth, Bråten, & Strømsø, 2016) whether mobile phone radiation can lead to cancer (Strømsø, Bråten, & Stenseth, 2017), and the topic of climate change (Stenseth, Bråten, & Strømsø, 2016). The topic we chose for this research concerned possible harmful and beneficial effects of sun exposure.…”
Section: Topic Used In the Empirical Studiesmentioning
confidence: 99%
“…Previous research has shown that individuals' pre-existing attitudes or opinions about a topic can heavily bias their information retrieval. Individuals seem to preferably access websites that provide attitudeconsistent rather than counterattitudinal information (e.g., Frost, Casey, Griffin, Raymundo, Farrell, & Carrigan, 2015;Knobloch-Westerwick, Johnson, & Westerwick, 2015;Schwind, Buder, Cress & Hesse, 2012), to judge proattitudinal information as more trustworthy (e.g., Bråten, Salmerón, & Strømsø, 2016;Strømsø, Bråten, & Stenseth, 2017;Van Strien, Kammerer, Brand-Gruwel, & Boshuizen, 2016), and also to better remember it (e.g., Frost et al, 2015;Maier & Richter, 2014;.…”
Section: Evaluating Information Encountered On Social Networking and mentioning
confidence: 99%